Retracted:-Identification of Benzoxazolinone Derivatives Based Inhibitors for Depression and Pain Related Disorders Using Human Serotonin and Norepinephrine Transporter as Dual Therapeutic Target: A Computational Approach - Selvaraj Manikandan; AR Saranya; Thirugnanasambandam Ramanathan; Krishnan Selvarajan Kesavanarayanan; LK Teh; MZ Salleh (International Journal of Phytomedicine, 2015)
Retracted:-Identification of Benzoxazolinone Derivatives Based Inhibitors for Depression and Pain Related Disorders Using Human Serotonin and Norepinephrine Transporter as Dual Therapeutic Target: A Computational Approach